State of Art of Solar Photovoltaic Technology. (30th May 2013) - Gangopadhyay, Utpal; Jana, Sukhendu; Das, Sayan
Abstract : Solar electricity is more expensive than that produced by traditional sources. But over the past two decades, the cost gap has been closing. Solar photovoltaic (SPV) technology has emerged as a useful power source of applications such as lightning, meeting the electricity needs of villages, hospitals, telecommunications, and houses. The long and increasing dominance of crystalline silicon in photovoltaic (PV) market is perhaps surprising given the wide variety of materials capable of producing the photovoltaic effect. PV based on silicon wafers has captured more than 90% market share because it is more reliable and generally more efficient than competing technologies. The crystalline silicon PV is reliable as far as long term stability in real field but it is not economically viable due to starting material silicon itself costly. But still, research continues on developing a diverse set of alternative photovoltaic technology. Now PV technology is being increasingly recognized as a part of the solution to the growing energy challenge and an essential component of future global energy production. In this paper, we give a brief review about PV technology particularly crystalline silicon PV including the world and Indian PV scenarios.